Arabidopsis Receptor of Activated C Kinase1 Phosphorylation by WITH NO LYSINE8 KINASE . Issue 2 (8th December 2014) - Urano, Daisuke; Czarnecki, Olaf; Wang, Xiaoping; Jones, Alan M.; Chen, Jin-Gui
Abstract : Phosphorylation of a scaffold protein negatively regulates its function by affecting protein stability. Abstract: Receptor of activated C kinase1 (RACK1) is a versatile scaffold protein that binds to numerous proteins to regulate diverse cellular pathways in mammals. In Arabidopsis ( Arabidopsis thaliana ), RACK1 has been shown to regulate plant hormone signaling, stress responses, and multiple processes of growth and development. However, little is known about the molecular mechanism underlying these regulations. Here, we show that an atypical serine (Ser)/threonine (Thr) protein kinase, WITH NO LYSINE8 (WNK8), phosphorylates RACK1. WNK8 physically interacted with and phosphorylated RACK1 proteins at two residues: Ser-122 and Thr-162. Genetic epistasis analysis of rack1 wnk8 double mutants indicated that RACK1 acts downstream of WNK8 in the glucose responsiveness and flowering pathways. The phosphorylation-dead form, RACK1A S122A/T162A, but not the phosphomimetic form, RACK1A S122D/T162E, rescued the rack1a null mutant, implying that phosphorylation at Ser-122 and Thr-162 negatively regulates RACK1A function. The transcript of RACK1A S122D/T162E accumulated at similar levels as those of RACK1 S122A/T162A . However, although the steady-state level of the RACK1A S122A/T162A protein was similar to wild-type RACK1A protein, the RACK1A S122D/T162E protein was nearly undetectable, suggesting that phosphorylation affects the stability of RACK1A proteins. Taken together, these results suggest that RACK1 is phosphorylated by WNK8 and that phosphorylation negatively regulates RACK1 function by influencing its protein stability.